PENERAPAN STRATEGI PEMBELAJARAN THE POWER OF TWO UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VC SD NEGERI 164 PEKANBARU - Yulia, Yona Yulia; Witri, Gustimal Witri; ', Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstact: This research is a classrom action research (PTK) wich aims to improve learning outcomes Maths grade student of VC SDN 164 Pekanbaru whit the implementation of the strategy The Power of Two. This research study presents the result obtained from the value of daily tests before treatment by an averageof 56,4, increasing to 75,11 in the first cycle, increased again to 79,28 in the second cycle, and increased again 80,23 in the third cycle. The research results prove that the application class Learning Strategies The Power of Two can improve students’ mathematics learning outcomes VC class SDN 164 Pekanbaru. Keywords: The Power of Two, Mathematics learning outcomes